Layered positive electrode material and preparation method and application thereof

CN120581587BActive Publication Date: 2026-09-08XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510910920.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-02
Publication Date
2026-09-08
Estimated Expiration
2045-07-02

AI Technical Summary

Technical Problem

[0003]本发明的目的在于针对现有的层状正极材料在高充电电压条件下的容量相比于总容量占比低的问题,而提供了一种层状正极材料及其制备方法和应用,该层状正极材料可以显著提高高充电电压条件下的容量在总容量中的占比,从而提高正极材料的整体容量性能

Benefits of technology

[0030] The key to this invention lies in first doping sodium into the layered cathode material precursor before performing lithium-sodium replacement. Simultaneously, during the sintering process required for sodium doping, the sintering is carried out in a sealed environment while the sodium source is in vapor form. This improves the stability of sodium, ensuring that it can effectively expand the layered structure of the material, increase the c-axis, and give the resulting layered cathode material a specific c-axis range. At this point, the increased c-axis of the material makes lithium ion insertion/extraction easier, and the presence of sodium stabilizes the material structure, thereby improving the capacity performance of the layered cathode material under high charging voltage conditions, i.e., during the H2-H3 phase transition process. This increases the proportion of capacity under high charging voltage conditions in the total capacity to over 14%, thereby improving the overall capacity performance of the cathode material and better meeting the application requirements of high energy density and long-range lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120581587B_ABST
    Figure CN120581587B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion batteries, and particularly relates to a layered positive electrode material and a preparation method and application thereof. The layered positive electrode material comprises a lithium-containing composite metal oxide with a layered structure and sodium ions doped in the lithium-containing composite metal oxide; a range of a c-axis of a crystal lattice parameter of the layered positive electrode material is 4.2-4.3 A; and a chemical general formula of the layered positive electrode material is Li m Na n (Ni x Co y Mn z )O2, wherein x+y+z=1 and m+n=1. The layered positive electrode material provided by the application can exert good capacity performance in a high charging voltage condition, i.e. in an H2-H3 phase change process, and the proportion of the capacity under the high charging voltage condition in the total capacity is increased to more than 14%, thereby improving the overall capacity performance of the positive electrode material and better meeting the application requirements of high energy density and high endurance lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a layered cathode material, its preparation method, and its application. Background Technology

[0002] Currently, lithium-ion battery cathode materials are classified into three categories based on their structure: layered cathode materials, spinel-type cathode materials, and olivine-structured cathode materials. Among them, layered cathode materials, such as lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO2), and lithium nickel oxide (LiNiO2), are widely used as cathode materials in small lithium-ion batteries due to their advantages such as high operating voltage, stable discharge, high specific capacity, and good cycle performance. They are also applied in portable electronic products such as mobile phones, tablets, and wearable devices. Generally speaking, the total capacity of a lithium battery depends on the total capacity of the cathode materials. However, existing layered cathode materials are prone to H2-H3 phase transitions (H2: spinel phase, H3: rock salt phase) at high charging voltages, such as 4.5–4.6V. The stress and lattice volume changes generated during this H2-H3 phase transition lead to microcracks in the material, accelerating electrolyte penetration and side reactions, ultimately resulting in rapid capacity decay. This results in a low proportion of capacity under high charging voltage conditions in the total capacity, which is detrimental to the overall capacity performance of the cathode material. Therefore, it is urgent to improve the capacity performance of layered cathode materials under high charging voltage conditions, thereby enhancing the overall capacity performance of cathode materials to meet market demands for high energy density and long-lasting lithium-ion batteries. Summary of the Invention

[0003] The purpose of this invention is to address the problem that the capacity of existing layered cathode materials is low relative to the total capacity under high charging voltage conditions, and to provide a layered cathode material, its preparation method, and its application. This layered cathode material can significantly increase the proportion of capacity in the total capacity under high charging voltage conditions, thereby improving the overall capacity performance of the cathode material.

[0004] In a first aspect, the present invention provides a layered cathode material. The layered cathode material comprises a lithium-containing composite metal oxide having a layered structure and sodium ions doped into the lithium-containing composite metal oxide; the range of the c-axis lattice parameter of the layered cathode material is... The chemical formula of the layered cathode material is Li. m Na n (Ni x Co y Mn z )O2, where x+y+z=1, m+n=1.

[0005] In a preferred embodiment, the chemical formula of the layered cathode material is 0.33≤x≤0.95, 0≤y≤0.33, 0.01≤z≤0.50, 0.9≤m≤0.95, and 0.05≤n≤0.1.

[0006] In a preferred embodiment, the specific surface area of ​​the layered cathode material ranges from 7 to 9 m². 2 / g.

[0007] In a preferred embodiment, the D50 particle size of the layered cathode material is 5–10 μm.

[0008] In a preferred embodiment, the sodium ion content in the layered cathode material is 1.0 to 2.1 wt%.

[0009] Secondly, the present invention provides a method for preparing the above-mentioned layered cathode material. The preparation method includes the following steps: S1. Mixing the layered cathode material precursor with a sodium source and then sintering it. During the sintering process, the sodium source is present in vapor form, and the sintering is carried out in a sealed environment. After sintering is completed, a semi-finished material is obtained; S2. The semi-finished material obtained in step S1 undergoes a hydrothermal displacement reaction with a lithium source. After the hydrothermal displacement reaction is completed, solid-liquid separation is performed, and the resulting solid is the layered cathode material. The chemical formula of the layered cathode material precursor is (Ni... x Co y Mn z )(OH)2, where x+y+z=1.

[0010] In a preferred embodiment, in step S1, the molar ratio of sodium ions in the sodium source to the total amount of metal ions in the layered cathode material precursor is (0.95~1.0):1.

[0011] In a preferred embodiment, in step S1, the sodium source is selected from at least one of sodium oxalate, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium acetate, sodium nitrate, sodium chloride, and sodium sulfate.

[0012] In a preferred embodiment, in step S1, the chemical formula of the layered cathode material precursor is 0.33≤x≤0.95, 0≤y≤0.33, and 0.01≤z≤0.50.

[0013] In a preferred embodiment, in step S1, the layered cathode material precursor is obtained by co-precipitation reaction of a nickel source, a manganese source, and optionally a cobalt source with an alkaline precipitant.

[0014] In a preferred embodiment, in step S1, the nickel source is selected from at least one of nickel oxalate, nickel carbonate, nickel acetate, nickel nitrate, nickel chloride, and nickel sulfate.

[0015] In a preferred embodiment, in step S1, the manganese source is selected from at least one of manganese oxalate, manganese carbonate, manganese acetate, manganese nitrate, manganese chloride, and manganese sulfate.

[0016] In a preferred embodiment, in step S1, the cobalt source is selected from at least one of cobalt oxalate, cobalt carbonate, cobalt acetate, cobalt nitrate, cobalt chloride, and cobalt sulfate.

[0017] In a preferred embodiment, in step S1, the alkaline precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia.

[0018] In a preferred embodiment, step S1, the sintering includes a first sintering and a second sintering performed sequentially, wherein the sodium source exists in solid form at the first sintering temperature and in vapor form at the second sintering temperature.

[0019] In a preferred embodiment, in step S1, the conditions for the first sintering include a temperature of 700–800°C and a time of 6–8 hours.

[0020] In a preferred embodiment, in step S1, the conditions for the secondary sintering include a temperature of 800–1000°C and a holding time of 11–13 hours.

[0021] In a preferred embodiment, in step S1, the gas inlet and outlet flow rates during the secondary sintering are within 3 L / min.

[0022] In a preferred embodiment, in step S1, the molar ratio of sodium ions in the semi-finished material to the total amount of metal ions in the layered cathode material precursor is (0.9-1.0):1.

[0023] In a preferred embodiment, in step S2, the hydrothermal replacement reaction includes mixing the lithium source with the reducing agent and water evenly, then heating the resulting premix to 80°C to 100°C and adding the semi-finished material, then introducing an inert gas into the resulting mixture to form an aerosol, and then heating the reaction system to 150°C to 170°C and reacting for 3 to 10 hours.

[0024] In a preferred embodiment, in step S2, the heating rates of the premix and the mixture are each independently 0.5 to 1.5 °C / min.

[0025] In a preferred embodiment, in step S2, the molar ratio of sodium ions in the semi-finished material to lithium ions and reducing agent in the lithium source is 1:(2.5-3.5):(0.1-0.2).

[0026] In a preferred embodiment, in step S2, the lithium source is selected from at least one of lithium nitrate, lithium chloride, lithium hydroxide, lithium bromide, lithium iodide, lithium sulfide, lithium fluoride, lithium carbonate, and lithium sulfate.

[0027] In a preferred embodiment, in step S2, the reducing agent is selected from at least one of lithium oxalate, vitamin C (VC), and sodium citrate.

[0028] In a preferred embodiment, the preparation method of the layered cathode material further includes washing the solid with water and drying it sequentially. The water added during the washing process has a mass ratio of water to solid of (1-3):1. The drying conditions include a temperature of 150℃ to 250℃ and a time of 5h to 20h.

[0029] Thirdly, the present invention also provides the application of the above-mentioned layered cathode material in lithium-ion batteries.

[0030] The key to this invention lies in first doping sodium into the layered cathode material precursor before performing lithium-sodium replacement. Simultaneously, during the sintering process required for sodium doping, the sintering is carried out in a sealed environment while the sodium source is in vapor form. This improves the stability of sodium, ensuring that it can effectively expand the layered structure of the material, increase the c-axis, and give the resulting layered cathode material a specific c-axis range. At this point, the increased c-axis of the material makes lithium ion insertion / extraction easier, and the presence of sodium stabilizes the material structure, thereby improving the capacity performance of the layered cathode material under high charging voltage conditions, i.e., during the H2-H3 phase transition process. This increases the proportion of capacity under high charging voltage conditions in the total capacity to over 14%, thereby improving the overall capacity performance of the cathode material and better meeting the application requirements of high energy density and long-range lithium-ion batteries. Detailed Implementation

[0031] The layered cathode material provided by this invention comprises a lithium-containing composite metal oxide with a layered structure and sodium ions doped into the lithium-containing composite metal oxide. The general chemical formula of the layered cathode material is Li. m Na n (Ni x Co y Mn z O2, where x+y+z=1, m+n=1, and x, y, z, m, and n satisfy the law of conservation of charge. The range of the c-axis lattice parameter of the layered cathode material is... like Or any value between them, more preferably as In this invention, the c-axis of the lattice parameter of the layered cathode material is obtained by XRD pattern fitting and refinement method, and the specific fitting process is known to those skilled in the art.

[0032] In this invention, in the general chemical formula of the layered cathode material, preferably, 0.33 ≤ x ≤ 0.95, where x can be 0.33, 0.4, 0.5, 0.51, 0.52, 0.53, 0.54, 0.55, or any value between them. Preferably, 0 ≤ y ≤ 0.33, where y can be 0, 0.1, 0.15, 0.2, 0.25, 0.3, 0.33, or any value between them. Preferably, 0.01 ≤ z ≤ 0.50, where z can be 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.33, 0.40, 0.50, or any value between them. Preferably, 0.9 ≤ m ≤ 0.95, where m can be 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, or any value between them. Preferably, 0.05≤n≤0.1, where n can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value between them.

[0033] In this invention, the specific surface area of ​​the layered cathode material is preferably in the range of 7 to 9 m². 2 / g, such as 7, 7.5, 8, 8.5, 9m 2 / g or any value therebetween. The D50 particle size of the layered cathode material is preferably 5–10 μm, such as 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any value therebetween. The term "D50 particle size" refers to the particle size corresponding to a cumulative particle size distribution percentage of 50% for a sample.

[0034] In this invention, the sodium ion content in the layered cathode material is preferably 1.0–2.1 wt%, such as 1.0 wt%, 1.2 wt%, 1.4 wt%, 1.45 wt%, 1.5 wt%, 1.55 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 2.0 wt%, 2.1 wt%, or any value between them, more preferably 1.2–1.8 wt%, and most preferably 1.4–1.6 wt%. The inventors of this invention have discovered that when the sodium ion content is controlled at 1.4–1.6 wt%, it has the advantage of a higher proportion of capacity in the total capacity under higher charging voltage conditions, giving the cathode material high capacity performance under high charging voltage conditions, i.e., during the H2–H3 phase transition process. This is because sodium can effectively expand the layered structure of the layered material, increase the c-axis, making lithium ion insertion / extraction easier while stabilizing the structure of the cathode material. When the sodium ion content is too high, although the c-axis increases further, there is a problem of insufficient lithium ions, resulting in a low overall capacity.

[0035] The method for preparing the layered cathode material provided by this invention includes the following steps:

[0036] S1. The layered cathode material precursor is mixed with a sodium source and then sintered. During the sintering process, the sodium source is in the form of vapor and the sintering is carried out in a closed environment. After the sintering is completed, a semi-finished material is obtained.

[0037] S2. The semi-finished material obtained in step S1 undergoes a hydrothermal replacement reaction with a lithium source. After the hydrothermal replacement reaction is completed, solid-liquid separation is performed, and the resulting solid is the layered cathode material.

[0038] In this invention, the sealed environment in step S1 refers to a relatively sealed environment. Specifically, it can refer to mixing the layered cathode material precursor with a sodium source, placing it in a container, and adding a cover plate to the top of the container to form a relatively sealed environment. Then, it is sent into a heating device for sintering. This allows the layered cathode material precursor to be placed under a higher sodium source vapor concentration during the sintering process when the sodium source is in the form of vapor. This is beneficial for sodium ions to enter the layered structure of the material to increase the c-axis.

[0039] In this invention, in step S1, the molar ratio of sodium ions in the sodium source to the total amount of metal ions in the layered cathode material precursor is preferably (0.95–1.0):1, such as 0.95:1, 0.96:1, 0.97:1, 0.98:1, 0.99:1, 1.0:1, or any value between them. This is more conducive to forming a structurally stable sodium-electric material with an O3 layered structure.

[0040] In this invention, the sodium source can be any existing compound that can provide sodium and can be used to prepare cathode materials, including but not limited to at least one of sodium oxalate, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium acetate, sodium nitrate, sodium chloride, and sodium sulfate.

[0041] In this invention, the general chemical formula of the layered cathode material precursor is (Ni x Co y Mn z(OH)₂, where x + y + z = 1. Preferably, 0.33 ≤ x ≤ 0.95, and x can be 0.33, 0.4, 0.5, 0.51, 0.52, 0.53, 0.54, 0.55 or any value between them. Preferably, 0 ≤ y ≤ 0.33, and y can be 0, 0.1, 0.15, 0.2, 0.25, 0.3, 0.33 or any value between them. Preferably, 0.01 ≤ z ≤ 0.50, and z can be 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.33, 0.40, 0.50 or any value between them. The layered cathode material precursor can be selected from at least one of nickel manganese oxide, nickel manganese sulfide, nickel manganese hydroxide, nickel cobalt manganese oxide, nickel cobalt manganese sulfide, nickel cobalt manganese hydroxide, nickel cobalt oxide, nickel cobalt hydroxide, cobalt manganese oxide, and cobalt manganese hydroxide. The layered cathode material precursor can be commercially available or prepared using various existing methods, specifically precipitation or solid-state methods. However, to ensure greater uniformity of the components and reduce surface alkali residue, thereby imparting better capacity and capacity retention to the battery, co-precipitation is preferred. Specifically, the co-precipitation method generally involves co-precipitating a nickel source, a manganese source, and optionally a cobalt source with an alkaline precipitant. The order of addition of the nickel source, manganese source, and alkaline precipitant is not particularly limited; all materials can be added simultaneously; an alkaline precipitant can be used as the base solution, with the nickel and manganese sources added for reaction; or a mixture of nickel and manganese sources can be used as the base solution, with the alkaline precipitant added for reaction. Furthermore, the coprecipitation reaction is preferably carried out under stirring conditions. Additionally, after the coprecipitation reaction is complete, the resulting precipitate can be washed and dried.

[0042] In this invention, the amounts of the nickel source, cobalt source, and manganese source can be determined according to (Ni x Co y Mn z The molar ratio of nickel ions, cobalt ions, and manganese ions in the (OH)2 precursor is used to determine this.

[0043] In this invention, the alkaline precipitant contains OH... - The molar ratio of the total amount of metal ions in the nickel source, manganese source, and optionally cobalt source is preferably (2 to 2.5):1, such as 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, or any value between them.

[0044] In this invention, the preferred conditions for the coprecipitation reaction include: a temperature of 40–60°C, such as 40°C, 45°C, 50°C, 55°C, 60°C, or any value between them; a time of 40–60 h, such as 40 h, 45 h, 50 h, 55 h, 60 h, or any value between them; and a pH value of 10–11, such as 10, 10.2, 10.5, 10.8, 11, or any value between them.

[0045] In this invention, the nickel source can be any existing nickel-containing compound that can be used to prepare cathode materials, including but not limited to at least one of nickel oxalate, nickel carbonate, nickel acetate, nickel nitrate, nickel chloride, and nickel sulfate.

[0046] In this invention, the manganese source can be any existing manganese-containing compound that can be used to prepare cathode materials, and specific examples include, but are not limited to, at least one of manganese oxalate, manganese carbonate, manganese acetate, manganese nitrate, manganese chloride, and manganese sulfate.

[0047] In this invention, the cobalt source can be any existing cobalt-containing compound that can be used to prepare cathode materials, and specific examples include, but are not limited to, at least one of cobalt oxalate, cobalt carbonate, cobalt acetate, cobalt nitrate, cobalt chloride, and cobalt sulfate.

[0048] In this invention, the alkaline precipitant can be any existing variety capable of providing OH- - Compounds that cause nickel and manganese ions, and optionally cobalt ions, to precipitate, including but not limited to at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia.

[0049] In a preferred embodiment, step S1, the sintering includes a first sintering and a second sintering performed sequentially. The sodium source exists in a solid state at the first sintering temperature and in a vapor state at the second sintering temperature. This preferred sintering method has the advantages of more uniform sodium embedding, thereby increasing the c-axis and making the layered structure more stable. This is because step-by-step sintering allows sodium to be gradually embedded, ensuring that the sodium element uniformly enters and expands the layered structure of the material, further increasing the c-axis of the cathode material. The preferred conditions for the first sintering include a temperature of 700–800°C, such as 700°C, 720°C, 750°C, 780°C, 800°C, or any value between them; and a time of 6–8 hours, such as 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, or any value between them. The preferred conditions for the secondary sintering include a temperature of 800–1000℃, such as 800℃, 850℃, 900℃, 950℃, 1000℃, or any value between them; and a time of 11–13 hours, such as 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, or any value between them. During the secondary sintering process, the gas inlet and outlet flow rates are preferably controlled below 3 L / min. This is more conducive to retaining sodium in the sintering atmosphere, reducing loss, ensuring sufficient sodium element embedding and forming a layered structure, allowing the sodium element to effectively expand the layered structure of the material and increase the c-axis of the cathode material.

[0050] In this invention, in step S1, the molar ratio of sodium ions in the semi-finished material to the total amount of metal ions in the layered cathode material precursor is preferably (0.9-1.0):1, such as 0.9:1, 0.92:1, 0.95:1, 0.98:1, 1:1 or any value between them.

[0051] In this invention, in step S2, the molar ratio of sodium ions in the semi-finished material to lithium ions in the lithium source is preferably 1:(2.5 to 3.5), such as 1:2.5, 1:2.8, 1:3, 1:3.2, 1:3.5 or any value between them.

[0052] In this invention, the lithium source can be any existing lithium-containing compound that can be used to prepare cathode materials, and specific examples include, but are not limited to, at least one of lithium nitrate, lithium chloride, lithium hydroxide, lithium bromide, lithium iodide, lithium sulfide, lithium fluoride, lithium carbonate, and lithium sulfate.

[0053] In a preferred embodiment, step S2 involves uniformly mixing the lithium source with a reducing agent and water, then heating the resulting premix to 80°C–100°C, adding the semi-finished material, and then heating the resulting mixture to 150°C–170°C for 3–10 hours. More preferably, the hydrothermal replacement reaction involves uniformly mixing the lithium source with a reducing agent and water, then heating the resulting premix to 80°C–100°C, adding the semi-finished material, then introducing an inert gas into the resulting mixture to form an aerosol, and then heating the reaction system to 150°C–170°C for 3–10 hours. Preferably, the heating rates of the premix and the mixture are each independently 1.0–1.5°C / min, such as 1.0, 1.1, 1.2, 1.3, 1.4, 1.5°C / min or any value between them. This provides an advantage for a full reaction because excessively rapid heating is detrimental to a complete reaction. The preferred system temperature when the semi-finished material is added is 80℃~100℃, such as 80℃, 82℃, 85℃, 88℃, 90℃, 92℃, 95℃, 98℃, 100℃, or any value between them. At this temperature, the Li-Na exchange reaction rate is fast, and the material structure is not adversely affected by an overly vigorous displacement reaction. The preferred reaction temperature after the addition of the semi-finished material is 150℃~170℃, such as 150℃, 152℃, 155℃, 158℃, 160℃, 162℃, 165℃, 168℃, 170℃, or any value between them; the preferred reaction time is 3h~10h, such as 3h, 5h, 8h, 10h, or any value between them. Introducing an inert gas after adding the semi-finished material to form an aerosol further helps maintain the stability of the material structure while ensuring the smooth progress of the displacement reaction, thereby obtaining a cathode material with a larger c-axis. The inert gas is preferably at least one of nitrogen, argon, and xenon.

[0054] In this invention, in step S2, the molar ratio of sodium ions to reducing agent in the semi-finished material is preferably 1:(0.1-0.2), such as 1:0.1, 1:0.12, 1:0.15, 1:0.18, 1:0.2, or any value between them. The reducing agent can be any existing substance that facilitates the exchange of sodium in the semi-finished material with lithium in the lithium source, preferably at least one of lithium oxalate, vitamin C, and sodium citrate. Compared to other reducing agents (e.g., ether-based reducing agents), using at least one of lithium oxalate, vitamin C, and sodium citrate as the reducing agent avoids damage to the lattice structure of the cathode material, ensuring a complete lattice structure, which is more conducive to improving the charge / discharge capacity and capacity retention rate of the battery.

[0055] In a preferred embodiment, the preparation method of the layered cathode material further includes sequentially washing and drying the solid with water. The water-to-solid mass ratio added during the washing process is (1-3):1. This effectively controls the degree of washing because too little water affects efficiency, while too much water leads to over-washing. Maintaining the water-to-solid ratio within this range during washing effectively avoids over-washing. Specifically, the water-to-solid mass ratio added during washing can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, or any value between them. The washing process is preferably stopped when the ion concentration in the rinsing solution is less than 200 ppm. The drying conditions preferably include a temperature of 150℃ to 250℃, such as 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃ or any value between them; and a time of 5h to 20h, such as 5h, 8h, 10h, 12h, 15h, 18h, 20h or any value between them.

[0056] The present invention will be described in detail below through specific embodiments. These embodiments are intended to explain the invention and should not be construed as limiting it. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0057] Preparation Example 1

[0058] This preparation example illustrates a nickel-cobalt-manganese precursor (Ni 0.34 Co 0.33 Mn 0.33 The preparation of (OH)2 is as follows:

[0059] 154.76 g of nickel sulfate, 155.00 g of cobalt sulfate, and 151.00 g of manganese sulfate were weighed out according to a molar ratio of nickel ions, cobalt ions, and manganese ions of 1:1:1 and dissolved in deionized water to obtain a metal ion solution. 600 mL of a 10 mol / L sodium hydroxide solution was prepared as a precipitant according to a molar ratio of total metal ions to hydroxide ions of 1:2. Under conditions of 50℃ and pH 10, the sodium hydroxide solution was slowly added to the metal ion solution over 10 minutes to carry out a co-precipitation reaction for 50 hours, resulting in a suspension. The suspension was then filtered, washed, and dried to obtain the nickel-cobalt-manganese precursor (Ni). 0.34 Co 0.33 Mn 0.33 )(OH)2.

[0060] Preparation Example 2

[0061] This preparation example illustrates a nickel-cobalt-manganese precursor (Ni 0.90 Co 0.05 Mn 0.05 The preparation of (OH)2 is as follows:

[0062] 417.85 g of nickel sulfate, 23.25 g of cobalt sulfate, and 22.65 g of manganese sulfate were weighed and dissolved in deionized water according to a molar ratio of nickel ions:cobalt ions:0.05:0.05 to obtain a metal ion solution. 600 mL of a 10 mol / L sodium hydroxide solution was prepared as a precipitant, with a molar ratio of total metal ions to hydroxide ions of 1:2. The sodium hydroxide solution was slowly added to the metal ion solution over 10 minutes at 45 °C and pH 10.1, and a co-precipitation reaction was carried out for 60 hours to obtain a suspension. The suspension was filtered, washed, and dried to obtain the nickel-cobalt-manganese precursor (Ni). 0.80 Co 0.10 Mn 0.10 )(OH)2.

[0063] Preparation Example 3

[0064] This preparation example illustrates a nickel-cobalt-manganese precursor (Ni 0.55 Co 0.20 Mn 0.25 The preparation of (OH)2 is as follows:

[0065] 255.35 g of nickel sulfate, 93.00 g of cobalt sulfate, and 113.25 g of manganese sulfate were weighed and dissolved in deionized water according to a molar ratio of nickel ions:cobalt ions:0.20:0.25 to obtain a metal ion solution. 600 mL of a 10 mol / L sodium hydroxide solution was prepared as a precipitant, with a molar ratio of total metal ions to hydroxide ions of 1:2. The sodium hydroxide solution was slowly added to the metal ion solution over 10 minutes at 55°C and pH 10.5, and a co-precipitation reaction was carried out for 40 hours to obtain a suspension. The suspension was then filtered, washed, and dried to obtain the nickel-cobalt-manganese precursor (Ni). 0.55 Co 0.20 Mn 0.25 )(OH)2.

[0066] Preparation Example 4

[0067] This preparation example illustrates a nickel-manganese precursor (Ni 0.5 Mn 0.5 The preparation of (OH)2 is as follows:

[0068] 154.76 g of nickel sulfate and 151.00 g of manganese sulfate were weighed and dissolved in deionized water at a molar ratio of nickel ions to manganese ions of 1:1 to obtain a metal ion solution. 400 mL of a 10 mol / L sodium hydroxide solution was prepared as a precipitant at a molar ratio of total metal ions to hydroxide ions of 1:2. The sodium hydroxide solution was slowly added to the metal ion solution over 10 min at 55 °C and pH 10.5 to carry out a co-precipitation reaction for 40 h, resulting in a suspension. The suspension was then filtered, washed, and dried to obtain the nickel-cobalt-manganese precursor (Ni). 0.5 Mn 0.5 )(OH)2.

[0069] Example 1

[0070] This embodiment illustrates the preparation of a layered cathode material, and the specific process is as follows:

[0071] S1. Weigh out the nickel-cobalt-manganese precursor (Ni:Me, where Me includes Ni, Co, and Mn) obtained in Preparation Example 1 according to a molar ratio of Na:Me (Me includes Ni, Co, and Mn) of 0.95:1. 0.34 Co 0.33 Mn 0.33 (OH)2 and sodium carbonate are sintered together. The first sintering temperature is 750℃ and the sintering time is 7h. At the same time, the material needs to be removed and cooled to room temperature. Then, a second sintering is carried out at 900℃ for 12h. During the second sintering process, a cover plate needs to be added to the top of the sagger, and the air intake and exhaust speed of the sintering furnace is controlled at 1.5L / min. After sintering, the material is crushed by jaw crusher, roller crusher, and sieved to obtain a semi-finished material. The molar ratio of Na:Me in the semi-finished material is 0.95:1.

[0072] S2. Lithium hydroxide and lithium oxalate reducing agent are dissolved in water to obtain a premix. The premix is ​​heated to 90°C at 1.2°C / min, and the semi-finished material obtained in step S1 is added and mixed evenly. Simultaneously, nitrogen gas is introduced into the solution at a flow rate of 33 L / min for 3 hours to ensure the presence of aerosols during the replacement process. The molar ratio of sodium ions in the semi-finished material to lithium ions in the replacement solution is 1:3, and the molar ratio of sodium ions to lithium oxalate reducing agent in the semi-finished material is 1:0.1. The resulting mixture is then heated to 160°C at 1.2°C / min for a hydrothermal reaction for 4 hours. After the reaction, solid-liquid separation is performed. The obtained solid is washed with water at a water-to-solid mass ratio of 1:2. Washing is stopped when the ion concentration in the washing solution reaches 180 ppm. The washed product is dried at 200°C for 10 hours to obtain a layered cathode material, denoted as Li. 0.93 Na0.07 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content is 1.50 wt%).

[0073] Example 2

[0074] This embodiment illustrates the preparation of a layered cathode material, and the specific process is as follows:

[0075] S1. Weigh out the nickel-cobalt-manganese precursor (Ni:Me) obtained in Preparation Example 2 according to a molar ratio of Na:Me (Me includes Ni, Co, and Mn) of 0.97:1. 0.90 Co 0.05 Mn 0.05 (OH)2 and sodium oxalate are sintered together. The first sintering temperature is 700℃ and the sintering time is 6h. At the same time, the material needs to be removed and cooled to room temperature. Then, a second sintering is carried out at 800℃ for 11h. During the second sintering process, a cover plate needs to be added above the sagger, and the air intake and exhaust speed of the sintering furnace is controlled at 2L / min. After sintering and discharge, the material is subjected to jaw crusher, roller crusher, and sieve treatment to obtain semi-finished material. The molar ratio of Na:Me in the semi-finished material is 0.93:1.

[0076] S2. Lithium hydroxide and VC reducing agent are dissolved in water to obtain a premix. The premix is ​​heated to 80°C at 1°C / min, and the semi-finished material obtained in step S1 is added and mixed evenly. Simultaneously, nitrogen gas is introduced into the solution at a flow rate of 33 L / min for 2.5 h to ensure the presence of aerosols during the replacement process. The molar ratio of sodium ions in the semi-finished material to lithium ions in the replacement solution is 1:3, and the molar ratio of sodium ions to lithium oxalate reducing agent in the semi-finished material is 1:0.15. The resulting mixture is then heated to 150°C at 1°C / min for hydrothermal reaction for 3 h. After the reaction, solid-liquid separation is performed, and the obtained solid is washed with water. During the washing process, the mass ratio of water to solid is controlled at 1:1. The washing is stopped when the ion concentration in the washing solution reaches 185 ppm. The washed product is dried at 200°C for 10 h to obtain a layered cathode material, denoted as Li. 0.94 Na 0.06 (Ni 0.90 Co 0.05 Mn 0.05 O2 (sodium content is 1.42 wt%).

[0077] Example 3

[0078] This embodiment illustrates the preparation of a layered cathode material, and the specific process is as follows:

[0079] S1. Weigh out the nickel-cobalt-manganese precursor (Ni:Me) obtained in Preparation Example 3 according to a Na:Me molar ratio of 1:1 (Me includes Ni, Co, and Mn). 0.55 Co 0.20 Mn 0.25 (OH)2 and sodium nitrate are sintered together. The first sintering temperature is 800℃ and the sintering time is 8h. At the same time, the material needs to be removed and cooled to room temperature. Then, a second sintering is carried out at 1000℃ for 13h. During the second sintering process, a cover plate needs to be added above the sagger, and the air intake and exhaust speed of the sintering furnace is controlled at 1L / min. After sintering and discharge, the material is subjected to jaw crusher, roller crusher and sieve treatment to obtain semi-finished material. The molar ratio of Na:Me in the semi-finished material is 0.98:1.

[0080] S2. Lithium hydroxide and sodium citrate reducing agent are dissolved in water to obtain a premix. The premix is ​​heated to 100℃ at 1.5℃ / min, and the semi-finished material obtained in step S1 is added and mixed evenly. Simultaneously, nitrogen gas is introduced into the solution at a flow rate of 33 L / min for 3.5 h to ensure the presence of aerosols during the replacement process. The molar ratio of sodium ions in the semi-finished material to lithium ions in the replacement solution is 1:3, and the molar ratio of sodium ions to lithium oxalate reducing agent in the semi-finished material is 1:0.2. The resulting mixture is then heated to 170℃ at 1.5℃ / min for hydrothermal reaction for 5 h. After the reaction, solid-liquid separation is performed. The obtained solid is washed with water, maintaining a water-to-solid mass ratio of 1:3. Washing is stopped when the ion concentration in the washing solution reaches 150 ppm. The washed product is dried at 200℃ for 10 h to obtain a layered cathode material, denoted as Li. 0.93 Na 0.07 (Ni 0.55 Co 0.20 Mn 0.25 O2 (sodium content is 1.58 wt%).

[0081] Example 4

[0082] Layered cathode materials were prepared according to the method of Example 1, except that the molar ratio of Na:Me (Me includes Ni, Co, and Mn) during the sintering of the feedstock in step S1 was 1.2:1, and the molar ratio of Na:Me in the semi-finished material was 1.17:1. All other conditions were the same as in Example 1. Layered cathode materials, denoted as Li, were thus prepared. 0.9 Na 0.1 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content is 2.50 wt%).

[0083] Example 5

[0084] Layered cathode materials were prepared according to the method of Example 1, except that in step S1, the nickel-cobalt-manganese precursor (Ni 0.34 Co 0.33 Mn 0.33 (OH)₂ and sodium carbonate were sintered directly at 900°C. During the sintering process, a cover plate was placed on top of the crucible. All other conditions were the same as in Example 1. This yielded a layered cathode material, denoted as Li. 0.95 Na 0.05 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content 1.20wt%).

[0085] Example 6

[0086] Layered cathode materials were prepared according to the method of Example 1, except that in step S1, the air intake and exhaust rates of the sintering furnace were controlled at 5 L / min during the secondary sintering. All other conditions were the same as in Example 1. The resulting layered cathode material was denoted as Li. 0.957 Na 0.043 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content 1.00wt%).

[0087] Example 7

[0088] Layered cathode materials were prepared according to the method of Example 1, except that in step S2, the same molar amount of tetrahydrofuran was used instead of lithium oxalate reducing agent. All other conditions were the same as in Example 1. The resulting layered cathode material was denoted as Li. 0.92 Na 0.08 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content 1.80wt%).

[0089] Example 8

[0090] Layered cathode materials were prepared according to the method of Example 1, except that in step S2, the semi-finished material was added before the premix was heated. All other conditions were the same as in Example 1. The resulting layered cathode material was denoted as Li. 0.927 Na 0.073 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content 1.70 wt%).

[0091] Example 9

[0092] Layered cathode materials were prepared according to the method of Example 1, except that in step S2, the semi-finished material was added when the premix was heated to 160°C. All other conditions were the same as in Example 1. The resulting layered cathode material was denoted as Li. 0.96 Na 0.04 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content 0.90wt%).

[0093] Example 10

[0094] Layered cathode materials were prepared according to the method of Example 1, except that in step S2, nitrogen gas was not introduced after the semi-finished material was added to the replacement solution. All other conditions were the same as in Example 1. The resulting layered cathode material was denoted as Li. 0.916 Na 0.084 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content 1.88wt%).

[0095] Example 11

[0096] Layered cathode materials were prepared according to the method of Example 1, except that in step S2, the heating rate of both the premix and the mixture was 3°C / min, while all other conditions were the same as in Example 1. The resulting layered cathode material was denoted as Li. 0.91 Na 0.09 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content 2.10 wt%).

[0097] Example 12

[0098] Layered cathode materials were prepared according to the method of Example 1, except that in step S1, the nickel-manganese precursor (Ni0.05:Me0.05, obtained in Preparation Example 4, was weighed according to a Na:Me (Me includes Ni and Mn) molar ratio of 0.95:1. 0.5 Mn 0.5 (OH)₂ was mixed with sodium carbonate and sintered under the same conditions as in Example 1, thereby preparing a layered cathode material, denoted as Li. 0.93 Na 0.07 (Ni 0.5 Mn 0.5 O2 (sodium content 1.6wt%).

[0099] Comparative Example 1

[0100] The reference layered cathode material was prepared according to the method of Example 1, except that in step S1, no sagger cover was added above the sagger during the secondary sintering. The molar ratio of Na:Me in the resulting semi-finished material was 0.89:1. All other conditions were the same as in Example 1. The reference layered cathode material, denoted as Li, was thus prepared. 0.978 Na 0.022 (Ni 0.34 Co 0.33 Mn 0.33 O2 (sodium content 0.50wt%).

[0101] Comparative Example 2

[0102] A reference layered cathode material was prepared according to the method of Example 1, except that in step S2, the molar ratio of sodium ions in the semi-finished material to lithium ions in the replacement solution was 1:5. All other conditions were the same as in Example 1. The resulting reference layered cathode material was denoted as Li(Ni) 0.34 Co 0.33 Mn 0.33 O2 (sodium content is approximately 0.00%).

[0103] Test case

[0104] This test example is used to illustrate the relevant performance of the layered cathode materials prepared by the above embodiments and comparative examples. The specific test methods are as follows and the results are shown in Table 1.

[0105] 1. Microstructure testing

[0106] (1) Test of lattice parameter c-axis: XRD test was performed on each layered cathode material, and the obtained XRD pattern was fitted and refined by TOPAS software to obtain c-axis data.

[0107] (2) Sodium content test: The sodium content of the obtained layered cathode material was tested by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0108] 2. Electrochemical performance testing

[0109] (1) Preparation of button cell: Layered positive electrode material, conductive agent Super P and binder PVDF were mixed in a mass ratio of 94:3:3. The viscosity of the slurry was controlled to be 8000 mPa·s in a degassing machine. Then, the slurry was uniformly coated on aluminum foil using an automatic coating machine to form the original electrode sheet. The electrode sheet was dried in a vacuum oven at 130°C for 4 hours, and then placed in a forced-air oven at 80°C for 12 hours to obtain the test sheet. Several small electrode sheets were cut from different positions of the above test sheet using a punch die with a diameter of 14 mm. Small electrode sheets with regular shape and smooth surface and edges were selected and weighed with a balance of 0.01%. The electrode sheets were placed in a vacuum drying oven and evacuated to 0.1 MPa to obtain the positive electrode sheet, which was then stored for later use. In an inert gas glove box with water and oxygen content of less than or equal to 0.0005%, coin cells were assembled according to the battery specifications of CR2023. The negative electrode was a lithium sheet, the separator was a polypropylene membrane, the high-voltage electrolyte solvent was a mixed solution of ethylene carbonate and diethyl carbonate with a volume ratio of 1:1, and the conductive salt was 1M lithium hexafluorophosphate. After assembly, the cells were encapsulated at 800 Pa for 5 seconds to obtain a coin cell.

[0110] (2) The total discharge capacity performance and the capacity ratio during the H2-H3 phase transition process were tested according to the following method:

[0111] A. The coin cell assembled according to the method in (1) is charged at a constant current of 0.1C to a voltage of 4.5V under normal temperature battery laboratory conditions, and then charged at a constant voltage of 4.5V to a current of 0.05C. After standing for 5 minutes, the charging capacity is recorded, and the first charging capacity at 0.1C is calculated. The coin cell is then discharged at a constant current of 0.1C to a voltage of 2.8V, and the discharge capacity is recorded. The first discharge capacity at 0.1C is calculated.

[0112] B. Calculate the relationship between dQ and dV (V refers to voltage) during the charging process of A above using the formula Q=I*T (Q refers to capacity, I refers to current, and T refers to time). This will yield the dQ / dV curve. By calculating the peak area in the 4.30~4.45V voltage range on the dQ / dV curve, the capacity Q1 of the H2-H3 phase transition process can be obtained. Then, calculate the proportion of capacity Q1 in the total charging capacity of A above.

[0113] Table 1

[0114]

[0115]

[0116] As shown in Table 1, compared with Comparative Example 1 and Comparative Example 2, the layered cathode material provided in this embodiment of the invention has a larger c-axis value and a higher capacity ratio in the H2-H3 phase transition process, exhibiting higher discharge capacity performance.

[0117] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention without departing from the principles and spirit of the present invention.

Claims

1. A layered cathode material, characterized in that, The layered cathode material comprises a lithium-containing composite metal oxide with a layered structure and sodium ions doped into the lithium-containing composite metal oxide; the lattice parameter c-axis of the layered cathode material ranges from 14.35 Å to 14.48 Å; the general chemical formula of the layered cathode material is Li. m Na n (Ni x Co y Mn z O2, wherein x+y+z=1, m+n=1, 0.33≤x≤0.95, 0.05≤y≤0.33, 0.01≤z≤0.50, 0.9≤m≤0.95, 0.05≤n≤0.1; the sodium ion content in the layered cathode material is 1.4~1.6wt%.

2. The layered cathode material according to claim 1, characterized in that, The specific surface area of ​​the layered cathode material ranges from 7 to 9 m². 2 / g.

3. The layered cathode material according to claim 1, characterized in that, The D50 particle size of the layered cathode material is 5~10μm.

4. A method for preparing the layered cathode material according to any one of claims 1 to 3, characterized in that, The preparation method includes the following steps: S1. The layered cathode material precursor is mixed with a sodium source and then sintered. During the sintering process, the sodium source is in the form of vapor and the sintering is carried out in a closed environment. After the sintering is completed, a semi-finished material is obtained. S2. The semi-finished material obtained in step S1 is subjected to a hydrothermal replacement reaction with a lithium source. After the hydrothermal replacement reaction is completed, solid-liquid separation is performed, and the resulting solid is the layered cathode material. The general chemical formula of the layered cathode material precursor is (Ni) x Co y Mn z )(OH)2, where x+y+z=1, 0.33≤x≤0.95, 0.05≤y≤0.33, 0.01≤z≤0.

50.

5. The method for preparing the layered cathode material according to claim 4, characterized in that, In step S1, the molar ratio of sodium ions in the sodium source to the total amount of metal ions in the layered cathode material precursor is (0.95~1.0):

1.

6. The method for preparing the layered cathode material according to claim 4, characterized in that, In step S1, the sodium source is selected from at least one of sodium oxalate, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium acetate, sodium nitrate, sodium chloride, and sodium sulfate.

7. The method for preparing the layered cathode material according to claim 4, characterized in that, In step S1, the layered cathode material precursor is obtained by co-precipitation reaction of a nickel source, a manganese source, and optionally a cobalt source with an alkaline precipitant.

8. The method for preparing the layered cathode material according to claim 7, characterized in that, In step S1, the nickel source is selected from at least one of nickel oxalate, nickel carbonate, nickel acetate, nickel nitrate, nickel chloride, and nickel sulfate; The manganese source is selected from at least one of manganese oxalate, manganese carbonate, manganese acetate, manganese nitrate, manganese chloride, and manganese sulfate. The cobalt source is selected from at least one of cobalt oxalate, cobalt carbonate, cobalt acetate, cobalt nitrate, cobalt chloride, and cobalt sulfate; The alkaline precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia water.

9. The method for preparing the layered cathode material according to claim 4, characterized in that, In step S1, the sintering includes a first sintering and a second sintering performed sequentially. The sodium source exists in solid form at the first sintering temperature and in vapor form at the second sintering temperature.

10. The method for preparing the layered cathode material according to claim 9, characterized in that, The conditions for the first sintering include a temperature of 700~800℃ and a time of 6~8h.

11. The method for preparing the layered cathode material according to claim 9, characterized in that, The conditions for the secondary sintering include a temperature of 800~1000℃ and a time of 11~13h.

12. The method for preparing the layered cathode material according to claim 9, characterized in that, The gas inlet and outlet flow rates during the secondary sintering are within 3 L / min.

13. The method for preparing the layered cathode material according to claim 4, characterized in that, In step S1, the molar ratio of sodium ions in the semi-finished material to the total amount of metal ions in the layered cathode material precursor is (0.9~1.0):

1.

14. The method for preparing the layered cathode material according to claim 4, characterized in that, In step S2, the hydrothermal replacement reaction includes mixing the lithium source with the reducing agent and water evenly, heating the resulting premix to 80°C~100°C and adding the semi-finished material, then introducing an inert gas into the resulting mixture to form an aerosol, and then heating the reaction system to 150°C~170°C and reacting for 3h~10h.

15. The method for preparing the layered cathode material according to claim 14, characterized in that, The heating rates of the premix and the mixture are each independently 1.0~1.5℃ / min.

16. The method for preparing the layered cathode material according to claim 14, characterized in that, The molar ratio of sodium ions to lithium ions and reducing agent in the semi-finished material is 1:(2.5~3.5):(0.1~0.2).

17. The method for preparing the layered cathode material according to claim 14, characterized in that, The lithium source is selected from at least one of lithium nitrate, lithium chloride, lithium hydroxide, lithium bromide, lithium iodide, lithium sulfide, lithium fluoride, lithium carbonate, and lithium sulfate.

18. The method for preparing the layered cathode material according to claim 14, characterized in that, The reducing agent is selected from at least one of lithium oxalate, vitamin C, and sodium citrate.

19. The method for preparing the layered cathode material according to claim 4, characterized in that, The method further includes sequentially washing and drying the solid, wherein the mass ratio of water to solid added during the washing process is (1~3):1, and the drying conditions include a temperature of 150℃~250℃ and a time of 5h~20h.

20. The layered cathode material according to any one of claims 1 to 3 is used in a lithium-ion battery.

Citation Information

Patent Citations

  • Preparation method of sodium ion battery positive electrode material

    CN118307045A

  • Lithium-nickel-manganese complex oxide, its manufacturing process and its application

    JP2008137837A